G75 'A Bolt from Blue – Be Aware!!'. (4th June 2013) - Guddeti, P; Crawford, M
Abstract : Aim: Prolonged QT syndrome is now recognised as a major cause of sudden unexpected cardiac death, especially in children and adolescents. Methods: Selected from Paediatric Cardiology clinic list Results: A 3 1/2 year old fit and healthy boy, was found to be unresponsive by his parents at home. He was given Cardio-pulmonary resuscitation(CPR) in Emergency dept as noted to have Ventricular Fibrillation(VF) rhythm and was given 2shocks. His total down time(from the onset of CPR to return of detectable pulse) was approximately 26mins. CT head were normal. In Cardiac ICU he was cardioverted twice using 60J energy and started on bolus dose of Amiodarone followed by maintenance dose. He was intubated total of 3days and was passively cooled for total of 72hrs. His ECG shown long QT syndrome and was started on Nadolol, titrated the dose based on serial 24hr tapes. His MRI head and Cardiac MRI was normal. His Cardiomyopathy screening blood tests were normal. His bloods were taken for Long QT syndrome genetic testing and was sent home with a consideration for inserting Intra cardiac defibrillator (ICD) when results available. ECG performed on both parents and his sister were normal. He was sent home with automated external defibrillator for parents to carry around. Parents were advised to attach 12 lead ECG probes to his body at night and oxygen saturation monitor. Parents and nursery staff received basic life support (BLS) training. His genetics blood tests came back positive for Long QT syndrome 3. Whole family was referred for genetics review and was listed for consideration of insertion of epicardial pacemaker. Conclusions: Long QT syndrome can be asymptomatic and be an incidental finding. However it can present as sudden syncope and malignant ventricular arrhythmia or sudden death in previously healthy individuals. All first degree family members of affected patients should be screened with ECG to determine whether others are affected. References: Moss AJ. Long QT Syndrome. JAMA2003; 289:2041–2044 Garson A Jr, Dick M 2nd, Fournier A, et al The long QT syndrome in children. An international study of 287 patients. Circulation1993; 87:1866–72